Animal lingui stics and the puzzl e of titi monkeys alarm sequence - Berthet, Mélissa; Benjumea, Juan; Millet, Juliette; Cäsar, Cristiane; Zuberbühler, Klaus; Dunbar, Ewan (Proceedings of the Amsterdam Colloquium, 2019)
This article aims to illustrate how animal linguisti cs can increase our understanding of animal communication using the example of the alarm system of Black-fronted titi monkeys. Titi monkeys produce sequences composed of A- and B-calls in alarm situati ons. Previous biological and linguisti c works investigated the semantics of these utterances but reli ed on a preliminary dataset. We followed up on this work by carrying out an extensive analysis of meaning at the call and sequence level, based on 18 months of field observations and experiments followed by acoustical and linguisti c analyses. Our results suggest that alarm calls refer to the emotional state of the caller at the time of emission of the call. Listeners most likel y attend to the proportion of BB-grams in each sequence, which provides them with information about the caller’s emotional state, to infer what the predator is (aerial or terrestri al) and where it is (ground or canopy) using their world knowledge. Overall, this work suggests that the emotional states of animals can convey complex and reliable information to listeners. Our study illustrates that combining field data with linguistic anal yses provides a powerful new approach to better understand animal communication.